Come, join, lead: Attracting students to careers in aging and promoting involvement in gerontological societies. Issue 3 (3rd July 2018) - Moye, Jennifer; Molinari, Victor A.; Karel, Michele J.; Naik, Aanand D.; Sakai, Erin; Carpenter, Brian D.
ABSTRACT: Geriatric educators face the challenge of attracting more clinicians, scientists, and educators into geriatrics and gerontology, and promoting involvement in gerontological societies. A survey of psychologists ( N  = 100) examined factors that attract students in clinical/counseling psychology to practice with older adults, as well as experiences in organizational service. For 58%, interest in aging began at the undergraduate level, but for others interest developed later. About one half cited academic exposure such as mentorship (51%), research (47%), or coursework (45%) as sparking interest, along with family (68%) or work experience (61%). Involvement in professional organizations lags (58%), in part owing to misperceptions about what those activities require. A continued targeted effort at the undergraduate and graduate level is essential to attract students to careers in aging. To preserve vital professional organizations, enhanced outreach may be useful to dispel myths about service and encourage engagement.